Antimicrobial peptide-loaded gold nanoparticle-DNA aptamer conjugates as highly effective antibacterial therapeutics against Vibrio vulnificus. Issue 1 (December 2017) - Lee, Boeun; Park, Jonggwan; Ryu, Minkyung; Kim, Soochan; Joo, Minju; Yeom, Ji-Hyun; Kim, Suk; Park, Yoonkyung; Lee, Kangseok; Bae, Jeehyeon
Abstract Vibrio vulnificus causes fatal infections in humans, and antibiotics are commonly used in treatment regimens againstV. vulnificus infection. However, the therapeutic effects of antibiotics are limited by multidrug resistance. In this study, we demonstrated that an antimicrobial peptide (AMP), HPA3PHis, loaded onto a gold nanoparticle-DNA aptamer (AuNP-Apt) conjugate (AuNP-Apt-HPA3PHis ) is an effective therapeutic tool againstV. vulnificus infectionin vivo in mice. HPA3PHis induced bacterial cell death through the disruption of membrane integrity ofV. vulnificus . The introduction of AuNP-Apt-HPA3PHis intoV. vulnificus -infected HeLa cells dramatically reduced intracellularV. vulnificus by 90%, leading to an increase in the viability of the infected cells. Moreover, whenV. vulnificus -infected mice were intravenously injected with AuNP-Apt-HPA3PHis, a complete inhibition ofV. vulnificus colonization was observed in the mouse organs, leading to a 100% survival rate among the treated mice, whereas all the control mice died within 40 hours of being infected. Therefore, this study demonstrated the potential of an AMP delivered by AuNP-Apt as an effective and rapid treatment option against infection caused by a major pathogen in humans and aquatic animals.